A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages had little chance to develop substantially during the war, will pass with the other responsibilities of that Act to the new joint authorities as a part of the general hospital and consultant service. Venereal diseases The service for venereal diseases is at present in the hands of the county and county borough councils, and its allocation between those authorities and the new joint authority presents difficulty. In one sense it is essentially a clinic service which could continue to be locally organised within the framework of the new general area plan and need not be regarded as part of the wider hospital and consultant field. The newly developing use — started during the war — of the help of individual general practitioners to supplement the work of the clinics lends some point to this. On the other hand, it is a service requiring a high degree of specialisation and it is as a matter of convenience one which is usually attached to hospital premises; these are factors which point to associating it with the reorganised hospital service. It is something of a "border-line" case, and will be best left to be determined in the settlement of the area plan in each case. New Services Home nursing. A full home nursing service must be one of the aims of the new service. How far it needs to be directly provided by public authority, or indirectly by arrangements made with other bodies, or both, will be matters for discussion. Its object must be to ensure that those who need nursing attention in their homes will be able to obtain it without charge through the new service. It is contemplated that the task of securing this will be entrusted to county and county borough councils. Dental and ophthalmic services. A full dental service for the whole population, including regular conservative treatment, must unquestionably form part of the new National Health Service. But there are not at present, and will not be for some years to come, enough dentists in the country to provide it. Until the supply can be increased attention will have to be concentrated on priority needs. These must include the needs of children and young people, of expectant and nursing mothers, and it is these needs which must first be met. The whole dental problem is a peculiarly difficult one, and a Committee under the chairmanship of Lord Teviot has been set up by the two Health Ministers to consider and report on it. There may be similar (though perhaps less acute) difficulties in getting a full service in ophthalmology. But these, like the difficulties in dentistry, must be treated rather as practical problems arising in the operation of a new service than as matters of doubt in planning its scope and objectives. Health Centres. The arrangements for the local provision of Health Centres have been already mentioned as the responsibility normally of the county and county borough councils. 20 36/H24/41